Atividade virucida de porfirinas tetra-platinadas frente a vírus de bovinos - Basso, Giovana (2018)
Porphyrins are photosensitizing (PS) substances, that is, compounds that are activated when exposed to light, reacting with oxygen molecules and producing reactive oxygen species (ROS). The porphyrins are composed of four pyrrole rings joined together by methenyl bridges, forming an aromatic tetrapyrrole macrocycle. Photodynamic inactivation is a simple and controllable method, and is based on ROS production, which can be free radicals and/or singlet oxygen ( 1O2). This process requires the combined action of oxygen, light and a photosensitizer (PS). Photodynamic therapy has been used in the treatment of tumors and infectious disease. Due to microbial resistance to many commercial drugs, the search for new drugs has become a necessity and the use of porphyrins has gained prominence. The objective of this work was to evaluate the virucidal activity of two tetra-platinized porphyrins (3 and 4-PtTPyP) in different animal viruses. The cytotoxicity of the compounds was determined by the MTT test and, from the higher non-toxic concentration for cultured cells, lower concentrations of porphyrins were used in the virucidal tests. Virucidal tests were performed with DNA viruses with envelope (bovine herpesvirus type 1, BoHV-1) or non-enveloped (bovine adenovirus, BAV) and RNA viruses with envelope (and bovine viral diarrhea virus, BVDV) and non-enveloped (bovine enterovirus, BEV). In addition, virucidal activity was investigated against vaccinia virus (VACV, DNA virus enveloped) and vesicular stomatitis (VSV, RNA virus enveloped), which are epitheliotropic viruses that cause important economic and sanitary impact on bovine production. For this, viral suspensions of known viral concentration were incubated with the porphyrins and exposed to light for different time periods (0, 15, 30 and 60 min). After this, viral titers were determined by limiting dilution and compared to viral control. Virucidal assays using 3-PtTPyP porphyrin at the highest concentration (9.1μM) resulted in total inactivation of enveloped viruses even when not exposed to light. The use of 1/10 of the dose of the same porphyrin (0.91 μM) resulted in a reduction in the titer of BVDV and VSV virus after 15 min of light exposure, and total inactivation was observed after 30 min. For BoHV-1 and VACV, total inactivation occurred after 60 min of photoactivation. The use of 9.1 μM 4-PtTPyP also resulted in total inactivation of the enveloped BoHV-1, BVDV and VSV, even without photoactivation. For the enveloped VACV complete inactivation occurred after 15 min of light exposure. When 4-PtTPyP was used in a lower concentration (0.91 μM) gradual reduction in infectivity of enveloped virus was observed according to the time of light exposure. In addition, there was a significant loss of viral infectivity when the virus were incubated with the compound without photoactivation, but viral inactivation was only partial. None of the porphyrins had virucidal activity on non-enveloped viruses. The results indicated that both porphyrins have virucidal activity on enveloped viruses, and can act directly on viral infectivity even when not activated by light, if used in high concentrations.